2013
DOI: 10.1242/dev.092833
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis HD-Zip II transcription factors control apical embryo development and meristem function

Abstract: SUMMARYThe Arabidopsis genome encodes ten Homeodomain-Leucine zipper (HD-Zip) II proteins. ARABIDOPSIS THALIANA HOMEOBOX 2 (ATHB2), HOMEOBOX ARABIDOPSIS THALIANA 1 (HAT1), HAT2, HAT3 and ATHB4 are regulated by changes in the red/far red light ratio that induce shade avoidance in most of the angiosperms. Here, we show that progressive loss of HAT3, ATHB4 and ATHB2 activity causes developmental defects from embryogenesis onwards in white light. Cotyledon development and number are altered in hat3 athb4 embryos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
172
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(176 citation statements)
references
References 80 publications
3
172
1
Order By: Relevance
“…Previous studies have shown that the HD-ZIPII genes HAT3 and ATHB4 play an essential role in establishing leaf polarity by promoting adaxial cell fate (5,6). Although HAT3 and ATHB4 are known to be downstream targets of the HD-ZIPIII transcription factor REVOLUTA (14), we further investigated the relationship between these genes by monitoring the expression of REV in the hat3 athb4 double mutant (6) using the functional fluorescent reporter pREV::REV-2xYPET.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the HD-ZIPII genes HAT3 and ATHB4 play an essential role in establishing leaf polarity by promoting adaxial cell fate (5,6). Although HAT3 and ATHB4 are known to be downstream targets of the HD-ZIPIII transcription factor REVOLUTA (14), we further investigated the relationship between these genes by monitoring the expression of REV in the hat3 athb4 double mutant (6) using the functional fluorescent reporter pREV::REV-2xYPET.…”
Section: Resultsmentioning
confidence: 99%
“…To gauge the relative importance of MIR165/166 regulation to overall HD-ZIPII protein function, we transformed a miR165/166-resistant REV reporter (pREV::REVr-2xVENUS), as well as a miRsensitive REV reporter (pREV::REV-2xVENUS), into hat3 athb4 and hat3 athb4 athb2 plants (6) and assessed the degree of phenotypic rescue by REVr compared with the control. Compared with the miR-sensitive REV reporter ( (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AS2 also directly suppresses ETT expression in the adaxial domain (13). However, HD-ZIPIII directly activates the expression of HD-ZIPII genes in the adaxial domain (14,15). It is conceivable that incipient leaf primordia may be prepatterned into adaxial and abaxial domains (16), because REV and KAN1 are restricted very early to the adaxial domain and the abaxial domain of incipient floral meristem, respectively (17,18).…”
mentioning
confidence: 99%
“…23 The HD-ZIP II family members are involved in various biological processes such as shade avoidance, meristem determination, leaf polarity, gynoecium and fruit development, auxin and other hormone responses. 23,[25][26][27][28][29] The fact that HAT1 and its close homologs, HAT2, HAT3, and HAT4 (ATHB-2), are BES1/BZR1 direct target genes, 3,4 prompt us to examine the function of the family transcription factors in BR responses. HAT1 and HAT3 are positive regulators for BR-regulated growth as double mutants of hat1 hat3 have reduced BR response in hypocotyl elongation assays and overexpression of HAT1 leads to increased stem elongation at the early stage of vegetative growth.…”
mentioning
confidence: 99%